PENYARINGAN HORIZONTAL SEBAGAI PELENGKAP BANGUNAN INSTALASI PENGOLAHAN AIR LIMBAH BATIK - Reja Framika; Koosdaryani Koosdaryani; Adi Yusuf Muttaqien (Matriks Teknik Sipil, 2014)
Fresh water is one of the basic human needs in a sustainable manner required. The use of Fresh water is essential for daily living such as householdand industrial. Fresh water is very difficult to obtain, because of the pollution of water river by household waste and industrial waste, whichcauses the water dirty and unfit for consumption prior to obtaining filtering process.. A breakthrough in technology is required to overcome thisproblem. In this case we are interested in using a mixture of quartz sand, rice husk, bamboo charcoal powder and zeolite as filter stone buildingand planning WWTP (wastewater treatment plant).The study was conducted at the Laboratory of Health Department of Civil Engineering Faculty of Engineering, University March Surakarta.While the location of sample testing conducted in Surakarta City Government Health Laboratory.. In the study the effectiveness of using the batikwastewater filter media of quartz sand, bamboo charcoal powder, rice husk and stone zeolite with 3 types: type 1 ratio of the thickness of thequartz sand, bamboo charcoal powder, rice husk and stone zeolite (8cm: 8cm: 8cm: 8cm) , type 2 quartz sand thickness ratio, bamboo charcoalpowder, rice husk and stone zeolite (8cm: 6cm: 10CM: 8cm), type 3 ratio of the thickness of quartz sand, bamboo charcoal powder, rice husk,zeolite stone (8cm: 10cm: 6cm: 8cm).The results showed that the effectiveness of filtering wastewater batik with a thickness ratio of quartz sand, bamboo charcoal powder, rice husk,and zeolite stone with horizontal filtering type 1 is able to reduce the pH level of the 8,53 into 7,38 with a percentage of 13.48%; COD of2724mg/lt be 454mg/lt with a percentage of 83.33%; copper of 1.17 mg / lt be 0.42 mg / lt with percentage of 64.10% and cyanide from0.052 mg / lt be 0.017 mg / lt with a percentage of 67.31% so as to enhance the filtering process is required design of building wastewater treatmentplant in order to more effectively. Planning of building wastewater treatment plant with: Waste Batik - Filtering - equalization - Unification- Aeration - Sedimentation - tub filter (quartz sand, bamboo charcoal powder, rice husk, and zeolite stone) - Lagoon. Design of wastewatertreatment plants getting maximum moment Mu = 1.25 Tm and Pu = 2.4099 T, columns with reinforcement 3D19, stirrups reinforcement ø83D19-70 mm, foundation reinforcement 4ø19-100mm, and worn floor plates reinforcement ø10 mm - 200 mm.